Pupillary responses to bright and dark stimuli in individuals with autism spectrum disorders. - Tomoe Hayakawa; Shun Nakano; Naoko Inada; Ayako Saneyoshi; Masaki Tsujita; Shinichiro Kumagaya; Naoto Hara (PLoS ONE)
Individuals with autism spectrum disorders (ASD) often exhibit difficulties in sensory processing, including visual hypersensitivity such as photophobia. This study investigates the neural mechanisms underlying photophobia in participants with ASD by analyzing pupillary responses. To achieve this, we examined the amplitude and velocity gradient (latency) of these responses. Pupillary responses were recorded using an eye-tracking system in participants with ASD (n =  17) and typically developing (TD) (n =  23). Stimuli alternated between bright (89.03 cd/m2) and dark (0.07 cd/m2) conditions following a dim state (2.75 cd/m2) with intervals of five seconds in Experiment 1 and 30 seconds in Experiment 2. The sensory profile test (AASP-J) showed that hypersensitivity was significantly defined in the ASD group than in the TD group. The pupillary response in the ASD group often featured missing values due to blinking during rapid alternation between bright and dark conditions, resulting in a decrease in the total number of participants. Specifically, only eight of the 17 participants in the ASD group and 20 of the 23 participants in the TD group remained for analysis in Experiment 1, and in Experiment 2, 15 of the 17 participants in the ASD group and 20 of the 23 participants in the TD group remained for analysis. In the dim state, pupillary diameter was large in the ASD and TD group in both experiments, while the pupil diameter decreased in the TD group in Experiment 2. In both experiments, maximum amplitude and its latency showed no significant differences between the two groups. However, the velocity gradient for the early mydriatic process in the dark condition was significantly faster in the ASD group. ASD individuals with hypersensitivity tend to have large pupil diameters under the dim state, as well as rapid dilation in the dark condition. These results may suggest a problem in the sympathetic nervous system, which controls pupil constriction.